An analysis on the misuse of international student pass which violates the Malaysian Immigration Act 1959/63 / Siti Atifah Mohd Zin, Izzatul Izreen Mansor and Norhazurin Fazaieti Asrul Efandi - Mohd Zin, Siti Atifah; Mansor, Izzatul Izreen; Asrul Efandi, Norhazurin Fazaieti (2014)
This research aims to identify the problems that arise in Malaysia pertaining to the abuses of student passes. The research method entails a comparative study between Malaysia, United Kingdom, Singapore and Brunei immigration statutes. It also analyses the procedures in granting student passes in four stated countries. The research methodology is doctrinal in nature, focusing on library based materials. The findings reveal that the Malaysian Immigration Act 1959/63 and the procedures in granting student passes are not as stringent or effective compared to those of Singapore and United Kingdom. It is recommended that Malaysia should implement biometric documentations, application of visas online and computerized databases for international students. It should also introduce more stringent corporal punishment and implement a system similar to the Student and Exchange Visitor Information System (SEVIS) of the United States in granting student passes.